Financial Federalism in Pakistan: Implications for Centre-Province Relations - Prof. Dr. Iram Khalid; Ms. Nusrat Hussain (Journal of Political Studies, 2018)
This paper explores the development in financial federalism of Pakistan through execution of NFC Awards. Improvement and mutual consensus in fiscal matters are not only vital for the overall economic wellbeing of a federation but also for its integration. An overview of federal governments in the world provided economically stronger center with comparatively less resourceful units.Pakistan like other federations of the world has gone through many ups and downs but still matters are to be settled. Wide economic differences in provinces have made collection and sharing of revenue complicated. Efforts in the NFC Awards are not revolutionary butA slow change to remove vertical and horizontal imbalances has been observed. Eighteenth amendment has helped provinces to obtain the revenue from local sources as well for devisable pool.Delay in next NFC Award points out that Fiscal federalism still needs interprovince coordination and more efforts for exploration of local resources. A national political debate along with economic realities are needed to regulate the process of NFC Awards. Pakistan can consider Canadian fiscal federalism to improve some issues highlighted in NFC debates. Execution of a just and acceptable Award will improve fiscal federalism as well as political federalism of Pakistan.